2021
DOI: 10.1017/wet.2021.21
|View full text |Cite
|
Sign up to set email alerts
|

Rice response to sublethal rates of paraquat, metribuzin, fomesafen, and cloransulam-methyl at different application timings

Abstract: Paraquat mixtures with residual herbicides before planting is a common treatment in Mississippi, and rice in proximity is susceptible to off-target movement of these applications. Four concurrent studies were conducted in Stoneville, MS, to characterize rice performance following exposure to a sub-lethal rate of paraquat, metribuzin, fomesafen, and cloransulam-methyl at different application timings. Applications were made to rice at spiking to one-leaf (VEPOST), two- to three-leaf (EPOST), three- to four-leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…By 4 WAT, injury was no greater than 5%, which was similar to decreasing injury in the current study with time. Paraquat applied at 10% of the labeled rate injured spike to 1-lf and 2-to 3-lf rice 44 to 47% at 1 and 2 WAT (Lawrence et al 2021). At 4 WAT, injury at these timings was still 45 and 42%, respectively, indicating slower recovery from paraquat injury early season than tiafenacil.…”
Section: Rice Injurymentioning
confidence: 92%
See 1 more Smart Citation
“…By 4 WAT, injury was no greater than 5%, which was similar to decreasing injury in the current study with time. Paraquat applied at 10% of the labeled rate injured spike to 1-lf and 2-to 3-lf rice 44 to 47% at 1 and 2 WAT (Lawrence et al 2021). At 4 WAT, injury at these timings was still 45 and 42%, respectively, indicating slower recovery from paraquat injury early season than tiafenacil.…”
Section: Rice Injurymentioning
confidence: 92%
“…Patterson et al (2023) reported that drill-seeded rice was more tolerant to application of benzobicyclon at the 4-lf or tillering growth stages than early growth stages. Lawrence et al (2021) investigated the impacts of foliar application of sublethal rates of paraquat, a non-selective contact herbicide similar to tiafenacil, and fomesafen, a PPO herbicide like tiafenacil, to rice at the spike through panicle differentiation growth stage. Fomesafen injury three DAT exceeded 11% only with a preflood application.…”
Section: Introductionmentioning
confidence: 99%
“…Factor A was labeled herbicide treatment and consisted of no herbicide treatment and the herbicide products listed in Table 2 applied to rice in the three- to four-leaf (MPOST) growth stage. Factor B was paraquat (Gramoxone SL; Syngenta Crop Protection, Greensboro, NC) exposure and consisted of paraquat applied at 0 and 84 g ha −1 to rice at the spiking to one-leaf (VEPOST) stage (Lawrence et al 2020a,b; 2021). Simulated off-target movement tested with constant carrier volume was used reduced herbicide rates to simulate low concentration exposure (Davis et al 2011; Ellis et al 2002; Lawrence et al 2020b; McCoy et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…There is no label for metribuzin for use in rice in California. Although information regarding the effect of metribuzin application rates and timing on weed control in rice is scant, recent studies from Mississippi have indicated that metribuzin applied post rice emergence at 42 g ai ha −1 caused 36% injury by 28 d after treatment (DAT) (Lawrence et al 2021). The same study found no correlation between rice injury from metribuzin and yield reduction, dry weight reduction, maturity delays, or seed germination (Lawrence et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although information regarding the effect of metribuzin application rates and timing on weed control in rice is scant, recent studies from Mississippi have indicated that metribuzin applied post rice emergence at 42 g ai ha –1 caused 36% injury by 28 d after treatment (DAT) (Lawrence et al 2021). The same study found no correlation between rice injury from metribuzin and yield reduction, dry weight reduction, maturity delays, or seed germination (Lawrence et al 2021). Mahajan and Chauhan (2022) evaluated metribuzin at rates 72 and 144 g ai ha –1 and were able to reduce jungle rice [ Echinochloa colona (L.) Link] biomass by 70% and 100%, respectively, compared to the untreated control.…”
Section: Introductionmentioning
confidence: 99%